The Cryptocurrency Market in Kenya: A Review of Awareness and Participation by the Youth - Kamau, Charles Guandaru (Journal of Asian Business Strategy, 2022)
This study examines Kenyan youths’ level of knowledge and involvement in the cryptocurrency industry. Digital currencies, known as cryptocurrencies, use a peer-to-peer technology to speed up internet transactions. The idea of cryptocurrencies started in the 1980s but has since developed significantly. The study collected secondary data and conducted online surveys. In this study, panel data from four different cryptocurrencies’ values, transaction fees, and volumes over a six-year period were studied. The findings indicate a connection between the number of cryptocurrency transactions, their prices, and their transaction costs. The research also demonstrates how much the youth in Kenya are aware of and use cryptocurrencies. This paper also highlights some factors that may be considered when engaging in crypto business. It also highlights some of the principal properties of cryptos. The study concludes that there is a need for both local and international regulation of the cryptocurrency market to boost investor confidence and improve security.